Fertility in Portugal, How persistent is it? - Mendes, Maria Filomena (2013)
The decline in fertility that has been observed in Portugal is an apparent fact. From 1960 to 2002, the average number of children by woman has decreased from 3.1 to 1.5. Not ignoring this strong evidence of a sustainable decrease in fertility, the fact is that the numbers on the fertility rates by women’ ages show different realities. At the first sight, the decline in fertility of younger women has been the result of a postponement of births given that a general increase in fertility rates has been observed for older women. A question that then comes up is the following: are these observed trajectories sustainable in the sense of reflecting persistence in time or are just mere phases of a cycle in fertility? The paper intents to start giving an answer to that question by the use of statistical techniques, in a univariate approach, which are adequate to measure the degree of persistence over time.